Perancangan Ulang Map Rekam Medis Di Puskesmas Glugur Darat Medan 2022 - Mei Sryendang Sitorus; Bella Siringo-ringo (Akademi Perekam dan Informasi Kesehatan Imelda, 2023)
Medical record folder is a folder that is used to protect the forms in it to facilitate storage, especially patient medical record forms. The medical record folder at the Glugur Darat Health Center in Medan is currently in the form of a landscape and uses pink cardboard which is easy to tear and does not last long. The purpose of this study was to analyze and design a medical record folder in terms of three aspects, namely the physical aspect of the form, the anatomical aspect of the form, and the aspect of form content at the Glugur Darat Health Center in Medan. This research method uses descriptive, qualitative methods with saturated sampling technique, which was carried out at the Glugur Darat Health Center Medan in July-September 2022. The subjects in this study were Medical Record Officers, Filing Officers and Registration Officers at the Glugur Darat Health Center Medan. The result of this study is the design of a medical record folder at the Glugur Darat Health Center in Medan which is viewed from three aspects, namely the physical aspect of the form, a medical record folder made of thin cardboard is easy to tear and not durable. In the anatomical aspect, the form was found to only contain the name of the Family Folder, the name of the Puskesmas and the logo of the Puskesmas in the Heading section. In the aspect of the contents of the form found in the medical record folder at the Glugur Darat Health Center Medan, there is no loading in the medical record folder with the words Confidential.